2012
DOI: 10.1039/c2sm25636c
|View full text |Cite
|
Sign up to set email alerts
|

Percolation and orientational ordering in systems of magnetic nanorods

Abstract: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG geförderten) Allianz- bzw. Nationallizenz frei zugänglich.This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.Based on Monte Carlo (MC) computer simulations we study the structure formation of a system of magnetic nanorods. Our model particles consist of fused spheres with permanent magnetic dipole moments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 59 publications
0
32
0
Order By: Relevance
“…The novel aspects of our contribution are the following. While others have investigated how the rod aspect ratio affects the phase behavior 27,34 we instead focus solely on the internal charge separation. We find that coarse gel-like structures form at high charge separations while denser aggregates form at low charge separations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The novel aspects of our contribution are the following. While others have investigated how the rod aspect ratio affects the phase behavior 27,34 we instead focus solely on the internal charge separation. We find that coarse gel-like structures form at high charge separations while denser aggregates form at low charge separations.…”
Section: Discussionmentioning
confidence: 99%
“…26 Alvarez and Klapp applied Monte Carlo simulations to systems of dipolar rods with permanent magnetic dipole moments modeled as fused magnetic dipolar spheres. 27 Additionally, they investigated rod-like particles with a longitudinal point dipole and found clusters of parallel rods as we do in our simulations at low charge distances. 28 Miller et al used molecular dynamics to investigate systems of dipolar dumbbells, representing the dipole-dipole interaction by a combination of a soft-sphere interaction and Coulombic interaction, and found that these particles aligned into head-to-tail chains.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, many types of unusual magnetic systems have been studied. Among them are magnetic rods and ellipsoids, 63,64 magnetic core-shell particles, 65 extended dipoles in the form of two overlapping, oppositely charged spheres, 66 linear molecules with shifted dipoles, 67 particles with magnetic caps, 68 particles interacting by higher moments then dipoles, 69 shifted-dipole particles moving in precessing magnetic fields, 70 and particles with embedded magnetic cubes. 71 Recently, we proposed an alternative way for creating a system with "unusual" properties.…”
Section: Introductionmentioning
confidence: 99%